Adipokines and Inflammation Alter the Interaction Between Rheumatoid Arthritis Synovial Fibroblasts and Endothelial Cells - Rebecca Hasseli; Klaus W. Frommer; Maria Schwarz; Marie-Lisa Hülser; Carina Schreiyäck; Mona Arnold; Magnus Diller; Ingo H. Tarner; Uwe Lange; Joern Pons-Kühnemann; Markus Schönburg; Stefan Rehart; et al. (Frontiers in Immunology, 2020)
Objective: The long-distance migration of rheumatoid arthritis synovial fibroblasts (RASFs) in the severe combined immunodeficiency (SCID) mouse model of rheumatoid arthritis (RA) suggests that an interaction between RASFs and endothelial cells (EC) is critical in this process. Our objective was to assess whether immunomodulatory factors such as adipokines and antirheumatic drugs affect the adhesion of RASFs to ECs or the expression of surface molecules.Methods: Primary ECs or human umbilical vein endothelial cell (HUVEC) and primary RASFs were stimulated with adiponectin (10 μg/mL), visfatin (100 ng/mL), and resistin (20 ng/mL) or treated with methotrexate (1.5 and 1,000 μM) and the glucocorticoids prednisolone (1 μM) and dexamethasone (1 μM), respectively. The expression of adhesion molecules was analyzed by real-time polymerase chain reaction. The interaction of both cell types was analyzed under static (cell-to-cell binding assay) and dynamic conditions (flow-adhesion assay).Results: Under static conditions, adipokines increased mostly binding of RASFs to EC (adiponectin: 40%, visfatin: 28%, tumor necrosis factor α: 49%). Under flow conditions, visfatin increased RASF adhesion to HUVEC (e.g., 0.5 dyn/cm2: 75.2%). Reduced adhesion of RASFs to E-selectin was observed after treatment with dexamethasone (e.g., 0.9 dyn/cm2: −40%). In ECs, tumor necrosis factor α (TNF-α) increased expression of intercellular adhesion molecule 1 (20-fold) and vascular cell adhesion molecule 1 (77-fold), whereas P-selectin was downregulated after stimulation with TNF-α (−6-fold).Conclusion: The adhesion of RASFs to EC was increased by visfatin under static and flow conditions, whereas glucocorticoids were able to decrease adhesion to E-selectin. The process of migration and adhesion of RASFs to ECs could be enhanced by adipokines via adhesion molecules and seems to be targeted by therapeutic intervention with glucocorticoids.